A development of online document retention system of course file / Norliyati Rohman - Rohman, Norliyati (2006)
Course file is a file contains all information of teaching instruction and education. Currently, Faculty of Information Technology and Quantitative Science (FTMSK) are using manual system in managing course file. Lecturer and administration staffs usually face some problems to access the course file either because of lack of security, loss of document or taking much time to access it. The purposes of this research are to identify user requirement, to design and to develop the Online Document Retention System of Course File. In order to elicit data of this research, two methodologies were used which are interview and questionnaire. The questionnaires were distributed among FTMSK's lecturers about 50 sets. The interviews were conducted to sample of stakeholder to gather the information. This system was developed by the intent of ease the process of accessing course file. Lecturers can use this system to upload and download any content of course file easily. But some features are not added such as imaging service where paper can easily scan and directly store into the system. By increasing some features hope that this system will be more useful in an organization.